Business Analysis and Product Innovation to Improve SMEs Business Performance - R A M Febrianti; A S N Herbert (Universitas Komputer Indonesia, 2022)
Currently, business growth, especially small and medium-sized businesses in Bandung City, Indonesia, has experienced a fairly high increase. In this era of the COVID-19 pandemic, SME players must be able to improve their analytical skills, especially knowledge about business trends. In addition, the innovation factor is also perceived to be very important in order to survive in the face of competition. This study is aimed to understand the influence of business analysis and innovation performance in improving the business performance of small and medium enterprises. This study uses a quantitative method with an explanatory approach to determine how much influence the independent variable has on the dependent variable. Respondents in this study were SMEs in the city of Bandung, especially on Jalan Cikutra. 200 questionnaires were distributed but only 170 were returned. The results in this study are that these two variables have a fairly high influence on business performance. This shows that the variables of business analysis ability and innovation are important factors for SMEs to improve their business performance